2021
DOI: 10.3390/molecules26144169
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Analysis, Toxicity Study, and Free-Radical Scavenging and Iron-Binding Assays Involving Coffee (Coffea arabica) Extracts

Abstract: We aimed to analyze the chemical compositions in Arabica coffee bean extracts, assess the relevant antioxidant and iron-chelating activities in coffee extracts and instant coffee, and evaluate the toxicity in roasted coffee. Coffee beans were extracted using boiling, drip-filtered and espresso brewing methods. Certain phenolics were investigated including trigonelline, caffeic acid and their derivatives, gallic acid, epicatechin, chlorogenic acid (CGA) and their derivatives, p-coumaroylquinic acid, p-coumaroyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 93 publications
1
8
0
Order By: Relevance
“…In C33A cells, aqueous GB or ethanolic SCG extracts seemed to increase cell viability; however, this does not necessarily indicate an increase in cell proliferation. Similar results have been described, as some metabolites contained in GB or SCG coffee extracts can increase enzymatic-mitochondrial activity, specifically a phytochemicals such as kahweol and cafestol, and CGAs can increase and potentiate mitochondrial-reducing enzymes and increased formazan products, which can result in higher percentages of cell viability [39]. Notably, the ethanolic extract from SCG diminished A549 cell viability only at 12.5 µg•mL −1 , the lowest concentration evaluated.…”
Section: Analysis Of In Vitro Antiproliferative Activity Morphologica...supporting
confidence: 83%
“…In C33A cells, aqueous GB or ethanolic SCG extracts seemed to increase cell viability; however, this does not necessarily indicate an increase in cell proliferation. Similar results have been described, as some metabolites contained in GB or SCG coffee extracts can increase enzymatic-mitochondrial activity, specifically a phytochemicals such as kahweol and cafestol, and CGAs can increase and potentiate mitochondrial-reducing enzymes and increased formazan products, which can result in higher percentages of cell viability [39]. Notably, the ethanolic extract from SCG diminished A549 cell viability only at 12.5 µg•mL −1 , the lowest concentration evaluated.…”
Section: Analysis Of In Vitro Antiproliferative Activity Morphologica...supporting
confidence: 83%
“…This study uses the method of Hutachok et al, and the method description partly reproduces their wording ( Hutachok et al, 2021 ). Venous blood (10 mL) was drawn from blood donors, collected in sodium heparin (158 USP units)-coated tubes, and diluted with sterile PBS at a 1:1 (v/v) ratio.…”
Section: Methodsmentioning
confidence: 99%
“…This study uses the MTT method of Hutachok et al, and the method description partly reproduces their wording ( Hutachok et al, 2021 ). In other words, the assay is based on the ability of the mitochondrial reductase system in live cells to change the yellow-colored MTT dye to a blue-colored formazan product.…”
Section: Methodsmentioning
confidence: 99%
“…resveratrol) obtained from red wine and catechins obtained from green tea (Camellia sinensis) 21 . Importantly, we have recently demonstrated that chlorogenic acid (CGA)-abundant coffee (Coffea arabica) extracts have exhibited ROS−scavenging and anti−cyclooxygenase (COX) activities, while inhibiting the aggregation of platelets in platelet−rich plasma (PRP) induced by ADP, collagen, epinephrine and arachidonic acid in a concentration−dependent manner 22,23 .…”
Section: Introductionmentioning
confidence: 99%